ASESMEN STRUKTUR GEDUNG BAJA EKSISTING BERDASARKAN ASCE 41-17 - Sutjipto, Suradjin; Sumeru, Indrawati; Supardjo, William; Sucipto, Sherrica Augustin (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2023)
Currently, every building is required to have a Certificate of Occupancy [Sertifikat Laik Fungsi (SLF) in Indonesian). Existing buildings are obligated to undergo a structural evaluation as a prerequisite to obtaining the SLF. Conducting a structural assessment for relatively old buildings, with limited available documents and without non-destructive test (NDT) due to budget constraints, poses a significant challenge. This paper will present an example of the evaluation results of an existing 3-story structural steel building in Jakarta. An analytical model of the structural system, approximating the actual condition of the existing building, was created based solely on visual observations, field measurements, and very limited information. Evaluations were then conducted using 3 procedures: ASCE 41-17 Tier 1, Tier 2, and proportional seismic forces, to obtain an overview of the building structure's strength and information on which location would experience the first structural failure in the event of a severe earthquake. The evaluation results indicate that the ductility requirements of seismic force-resisting system members and the strength of beam-column joint connections cannot meet the expected acceptance criteria. Using the results of this evaluation, decisions can be made for the next steps, such as strengthening the structure, limiting use, or demolishing the existing building.